Uma proposta de atuação educativa das Relações públicas: manual para sobrevivência dos colaboradores no mundo digital - Marques, Yuri Samorano [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Society is increasingly connected to the virtual world, this is reflected in the number of people who spend a good part of their time connected on digital social media, including company employees (regardless of whether they are working hours or not). Thus, it is necessary that such employees take great care with what they will post on their social networks as it can affect the image of the organization in which they work. This is something that has been worrying companies due to high competition in the market and public opinion is increasingly demanding about what they consume. Therefore, this course conclusion work, in the form of an experimental project, aims to create an educational audiovisual manual (web series) to inform and instruct the internal public of organizations on the best ways to use social media. Such internal communication action is intended to develop the communicational and informational competence in employees so that, together with organizations, they are critical in the use of their media. For this to be done, the project is based on Corporate Education, as it is one of the possibilities for Public Relations professionals to act when organizations need to be trained in the area of communication. In order to provide a theoretical basis, important concepts were addressed, such as corporate education, internal public and organizational image for contextualization. Right after that, the audiovisual piece was presented, which was designed in a web series format, but which will be presented with a pilot based on the episode. three. It is concluded that there is a need to work on the communication of organizations through corporate education, having as a precept the influence that the internal public has on the image and reputation of companies and as the lack of working with them, mainly in the media can create a negative image.

A sociedade está cada vez mais conectada ao mundo virtual, isso é refletido na quantidade de pessoas que passam boa parte do seu tempo nas mídias sociais digitais, inclusive colaboradores das empresas (independente se estão em horário de trabalho ou não). Dessa forma, é preciso que tais funcionários tomem todo o cuidado com o que irão postar em suas redes sociais pois pode afetar na imagem da organização em que eles trabalham. Isso é algo que vem preocupando as empresas devido a alta concorrência do mercado e da opinião pública estar cada vez mais exigente sobre o que consome. Sendo assim, esse trabalho de conclusão de curso, na modalidade de projeto experimental, tem o intuito de criar um manual audiovisual educativo (websérie) para informar e instruir o público interno de organizações sobre as melhores formas de se utilizar as mídias sociais. Tal ação de comunicação interna tem a intenção de desenvolver a competência comunicacional e informacional nos colaboradores para que, juntamente com as organizações, eles sejam críticos no uso de suas mídias. Para que isso seja feito, o projeto está pautado na Educação Corporativa, visto que é uma das possibilidades de atuação do profissional de Relações Públicas quando as organizações precisam se capacitar na área da comunicação. Para dar embasamento teórico foram abordados conceitos importantes, tais como educação corporativa, público interno e imagem organizacional para a contextualização e logo após disso é exposta a peça audiovisual, a qual foi pensada em formato de websérie, mas que será apresentado um piloto baseado no episódio três. Conclui-se que há a necessidade de trabalhar a comunicação das organizações através da educação corporativa, tendo como preceito a influência que o público interno possui para a imagem e reputação das empresas e como a falta de se trabalhar o assunto com eles, principalmente nas mídias sociais, pode criar uma imagem negativa.
A proposal for an educational role in Public Relations: a manual for the survival of employees in the digital world
Keywords: Public relations; Internal communication; Corporative education; Organizational image; Social networks; Audiovisual product; Relações Públicas; Comunicação interna; Educação corporativa; Imagem organizacional; Redes sociais; Produto audiovisual